2015
DOI: 10.1002/adem.201500222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg17Sr2 Phase on the Bio‐Corrosion Behavior of Mg–Zr–Sr Alloys

Abstract: The effect of the second phase Mg 17 Sr 2 on the biocorrosion behavior of Mg5ZrxSr (x ¼ 0, 2, 5 wt%) alloys before and after solution treatment was investigated. Electrochemical impedance spectroscopy, cathodic polarization and hydrogen evolution were used to evaluate the biocorrosion of Mg5ZrxSr. We found that Mg 17 Sr 2 precipitated on boundary zones and enhanced the galvanic effect, leading to a severer corrosion of the Mg matrix adjacent to Mg 17 Sr 2 . The corrosion subsequently spread gradually from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The results of the immersion tests confirmed that the galvanic effect is promoted in the interface area near Mg 17 Sr 2 fragments [ 18 ], which facilitates the corrosion of the Mg matrix adjacent to the intermetallic phase. With immersion time, corrosion-induced degradation gradually spreads from to the interior of Mg grains, which is consistent with the results reported in [ 35 ]. The highest corrosion rate of 0.91 mm/y after 30 days of immersion was observed in the coarse-grained state with manifestation of large and deep corrosion pits on the surface after a week of immersion.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the immersion tests confirmed that the galvanic effect is promoted in the interface area near Mg 17 Sr 2 fragments [ 18 ], which facilitates the corrosion of the Mg matrix adjacent to the intermetallic phase. With immersion time, corrosion-induced degradation gradually spreads from to the interior of Mg grains, which is consistent with the results reported in [ 35 ]. The highest corrosion rate of 0.91 mm/y after 30 days of immersion was observed in the coarse-grained state with manifestation of large and deep corrosion pits on the surface after a week of immersion.…”
Section: Discussionsupporting
confidence: 92%
“…Figure 1A shows the OM, SEM images and corresponding EDS diagram of the Mg-1Zn-1Sn and Mg-1Zn-1Sn-0.2Sr alloys. From the OM images, the grain size was slightly reduced from 26 ± 3 µm to 20 ± 2 µm with the incorporation of Sr, which is consistent with a previous study indicating that Sr has the effect of grain refinement [23][24][25]. With the addition of Sr, the second phase (bright spot) in the alloy matrix increases, the volume fraction of the second phase increased from 0.5% (Mg-1Zn-1Sn) to 1.1% (Mg-1Zn-1Sn-0.2Sr).…”
Section: Microstructures and Electrochemical Evaluationssupporting
confidence: 91%
“…In general, the corrosion of the Mg matrix primarily starts from the interfacial Mg matrix adjacent to the intermetallic phases. 36 Through analysis of the polarization tests on the Mg 17 Sr 2 and Mg 2 Dy phases, it can be seen that Mg 17 Sr 2 is relatively inert, as indicated by its higher corrosion potential and lower current density compared with those of Mg 2 Dy. Mg 2 Dy phases in grain boundaries may distribute at the interfaces between the Mg 17 Sr 2 intermetallic phase and the Mg matrix during rapid cooling (Figure 3).…”
Section: Corrosion Behavior Of Mg Alloysmentioning
confidence: 99%